cum se rezolva exercitiul (1+2+3+...+56)-(1+2+3+...36)?
Răspunsuri la întrebare
Răspuns de
0
1+2+3+.....+56=
56+55+54+....+1
S2=57X56
S2=3192
S=3192:2
S=1596
1+2+3+...+36
36+35+34+.....+1
S2=37X36
S2=1332
S=1332:2
S=666
1596-666=930
56+55+54+....+1
S2=57X56
S2=3192
S=3192:2
S=1596
1+2+3+...+36
36+35+34+.....+1
S2=37X36
S2=1332
S=1332:2
S=666
1596-666=930
Răspuns de
0
1+2+3+....+56=(56+1)*56:2=1596{suma lau gauss}
1+2+3+...+36=(36+1)*36:2=666
1596-666=930
1+2+3+...+36=(36+1)*36:2=666
1596-666=930
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Informatică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Fizică,
9 ani în urmă